2017
DOI: 10.1021/acs.jctc.6b01041
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Generation of Auxiliary Basis Sets

Abstract: A procedure was developed to automatically generate auxiliary basis sets (ABSs) for use with the resolution of the identity (RI) approximation, starting from a given orbital basis set (OBS). The goal is to provide an accurate and universal solution for cases where no optimized ABSs are available. In this context, "universal" is understood as the ability of the ABS to be used for Coulomb, exchange, and correlation energy fitting. The generation scheme (denoted AutoAux) works by spanning the product space of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
455
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 500 publications
(460 citation statements)
references
References 75 publications
4
455
0
1
Order By: Relevance
“…They retain the original DEF2 exponents but with contraction coefficients suitable for the DKH scalar relativistic Hamiltonian. Finally, the AUTOAUX feature was used to automatically generate auxiliary basis sets for the resolution of identity approximation (RI‐JK), which helps speed up the calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…They retain the original DEF2 exponents but with contraction coefficients suitable for the DKH scalar relativistic Hamiltonian. Finally, the AUTOAUX feature was used to automatically generate auxiliary basis sets for the resolution of identity approximation (RI‐JK), which helps speed up the calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The present DEF2-TZVPP basis sets are an adapted version of the DEF2 basis set from the Karlsruhe group (i.e.,A hlrichs basis set), which is provided in the Turbomole basis set library.T hey retain the original DEF2 exponents but with contraction coefficients suitable for the DKH scalar relativistic Hamiltonian. Finally,t he AUTOAUX feature [72] was used to automatically generate auxiliary basis sets for the resolution of identity approximation (RI-JK), [73] which helps speed up the calculations.…”
Section: Computationaldetailsmentioning
confidence: 99%
“…The initial structural optimisation of 4 was done using the coordinates obtained from the single crystal X‐ray data. The structure of the complex [ 4 Cu(II)] was optimized using the ORCA program with the pbe 6–31 g AutoAux functional and the 6–31G basis set . It was observed that Cu(II) is coordinated to the Schiff base through the phenolic oxygen and imine nitrogen atom resulting in the formation of a six‐membered cyclic ring structure that is coplanar to the salicylaldehyde moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Ionization energies of α‐phellandrene (8.12 eV), ocimene (8.38 eV), sabinene (8.48 eV) and myrcene (8.5 eV) were estimated using a method with the linear regression fit of the dependence of the known experimental IEs on the negative of the calculated energies of the highest occupied molecular orbital, HOMO . These were calculated using the ORCA 4.0 quantum chemistry package utilizing DFT BP86 with auxiliary def2/J basis sets under RI‐J approximation, yielding IE = 0.79 E HOMO [eV]+4.1906 (see Figure S2, supporting information). The optimized monoterpene geometries were also used to calculate polarizabilities and dipole moments (see Table S1, supporting information), which can be utilized for the calculations of reaction rate coefficients.…”
Section: Methodsmentioning
confidence: 99%